1997
DOI: 10.1073/pnas.94.8.4005
|View full text |Cite
|
Sign up to set email alerts
|

Differential utilization of CCR5 by macrophage and T cell tropic simian immunodeficiency virus strains

Abstract: Certain chemokine receptors serve as cofactors for HIV type 1 envelope (env)-mediated cell-cell fusion and virus infection of CD4-positive cells. Macrophage tropic (M-tropic) HIV-1 isolates use CCR5, and T cell tropic (Ttropic) strains use CXCR4. To investigate the cofactors used by simian immunodeficiency viruses (SIV), we tested four T-tropic and two M-tropic SIV env proteins for their ability to mediate cell-cell fusion with cells expressing CD4 and either human or nonhuman primate chemokine receptors. Unli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
165
2
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 213 publications
(181 citation statements)
references
References 46 publications
13
165
2
1
Order By: Relevance
“…These four Envs were also found to be just borderline or weakly positive for infection of human blood monocytes (Gao et al, 1996). As expected from previous studies (Chen et al, 1997 ;Edinger et al, 1997 ;Kirchhoff et al, 1997), the SIVmac239 Env mediated efficient entry into GHOST4 cells expressing CCR5, BOB\GPR15 or Bonzo\STRL33 (Fig. 1).…”
Section: Utilization Of Bonzo/strl33 and Bob/gpr15 By Hiv-1 Envssupporting
confidence: 69%
See 1 more Smart Citation
“…These four Envs were also found to be just borderline or weakly positive for infection of human blood monocytes (Gao et al, 1996). As expected from previous studies (Chen et al, 1997 ;Edinger et al, 1997 ;Kirchhoff et al, 1997), the SIVmac239 Env mediated efficient entry into GHOST4 cells expressing CCR5, BOB\GPR15 or Bonzo\STRL33 (Fig. 1).…”
Section: Utilization Of Bonzo/strl33 and Bob/gpr15 By Hiv-1 Envssupporting
confidence: 69%
“…Both laboratory-adapted and primary HIV-2 isolates often use CXCR4 (Owen et al, 1998). Surprisingly, in contrast to HIV-1 and HIV-2, different SIV strains use CCR5 but not CXCR4 (Chen et al, 1997 ;Edinger et al, 1997 ;Kirchhoff et al, 1997 ;Marcon et al, 1997). It has been shown, however, that some additional members of the 7TM family, Bonzo\STRL33, BOB\GPR15 and GPR1, support efficient entry of different SIV strains with differential ability to replicate in macrophages Deng et al, 1997 ;Farzan et al, 1997 ;Liao et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that high beta-chemokine levels correlate with the disease progression of SIV and HIV infections (25,27). It is worth noting that although SIVmac239 and SIVmac251 utilize CCR5 as their primary coreceptor, they can also use alternate coreceptors in vitro (8,15,17). Despite this ability to use alternate coreceptors in vitro, in vivo CCR5 seems to be the only coreceptor of consequence.…”
mentioning
confidence: 98%
“…Macrophages are permissive for M-tropic R5 and dual-tropic R5X4 but not prototype T-tropic X4 strains, although some primary X4 isolates can use macrophage CXCR4 (11,12). Conversely, all primary simian immunodeficiency virus strains use CCR5 for entry (13)(14)(15), but determinants in Env regulate their ability to proceed through postentry steps of infection in macrophages (16). The basis for cell-and strainspecific differences in macrophage coreceptor function is not known.…”
mentioning
confidence: 99%